Methodological contributions of a diaphasic oral corpus - Pérez Álvarez, Bernardo E. (Círculo de Lingüística Aplicada a la Comunicación, 2015)
This paper shows some of the methodological advantages of an oral corpus which allows for a comparison of different communicative situations. Our analysis is based on the Corpus Michoacano del Español, which contains oral data of more than 40 hrs. of recording and transcription, systematically collected following Koch and Oesterreicher’s (1985, 2001) model of language variation within the two poles of communicative immediacy and distance. An advantage of this corpus is that it facilitates a highly differentiated, qualitative as well as quantitative analysis of oral registers and “texts”. These and other methodological benefits are exemplified and discussed in the second part of the paper, in particular with respect to spatial deixis and some type of connective structures. Another point is to show that these and other structures typical of “written” monologic language, such as hypotaxis will be replaced by paratactic structures in oral language due to cognitive restrictions of the working memory, whenever there is a need to provide more information. The selection of different types of oral discourse situated on the axis between the two poles of communicative immediacy and distance argues for an integrated view of linguistic variation under the premise that variation can only be studied in “real life discourse”.
Keywords: Oral language; corpus linguistics; diafasia; variation